Bacterial zincophore [S, S]-ethylenediamine-N, N′-disuccinic acid is an effective inhibitor of MBLs. (23rd November 2017) - Proschak, Anna; Kramer, Jan; Proschak, Ewgenij; Wichelhaus, Thomas A
Abstract: Objectives: Carbapenemases such as MBLs are spreading among Gram-negative bacterial pathogens. Infections due to these MDR bacteria constitute a major global health challenge. Therapeutic strategies against carbapenemase-producing bacteria include β-lactamase inhibitor combinations. [ S, S ]-ethylenediamine- N, N ′-disuccinic acid (EDDS) is a chelator and potential inhibitor of MBLs. We investigated the activity of EDDS in combination with imipenem against MBL-producing bacteria in vitro as well as in vivo . Methods: The inhibitory activity of EDDS was analysed by means of a fluorescence-based assay using purified recombinant MBLs, i.e. NDM-1, VIM-1, SIM-1 and IMP-1. The in vitro activity of imipenem ± EDDS against mutants as well as clinical isolates expressing MBLs was evaluated by broth microdilution assay. The in vivo activity of imipenem ± EDDS was analysed in a Galleria mellonella infection model. Results: EDDS revealed potent MBL inhibitory activity against purified NDM-1, weaker activity against VIM-1 and SIM-1, and marginal activity against IMP-1. EDDS did not exhibit any intrinsic antibacterial activity, but enabled a concentration-dependent potentiation of imipenem against mutants as well as clinical isolates expressing various MBLs. The in vivo model showed a significantly better survival rate for imipenem + EDDS-treated G. mellonella larvae infected with NDM-1-producing Klebsiella pneumoniae compared with monotherapy with imipenem. Conclusions: The bacterial natural zincophore EDDS is a potent MBL inhibitor and in combination with imipenem overcomes MBL-mediated carbapenem resistance in vitro and in vivo .